A lesion mimicking melanoma of choroid [Koroi̇d melanomunu takli̇t eden bi̇r lezyon] - (:unkn) unknown (My University, 2007)
Radiological evaluations were performed as fundus examination was unavailable due to intravitreal hemorrhage in a case who came to our clinic with the complaint of an acute vision loss. Ultrasonography, doppler ultrasonography and magnetic resonance imaging reported that the retinal lesion was compatible with malignant melanoma. The patient underwent diagnostic vitrectomy due to rarity of vitreous hemorrhage with choroidal melanomas. Retinal examination revealed disciform lesion during vitrectomy.
Keywords: Choroidal melanoma; Differential diagnosis; Radiology